Job Hopping Tendency in Millenials - Pandey, Dhruba Lal (NCC Journal, 2019)
Job hopping refers to the tendency of a person to work briefly in an organization in particular position rather than staying in an organization for a longer time. This research study is conducted to examine the job hopping tendency in millennial in private sector of Nepal. It also studies the factors which attracts millennial in new organization. The factors which force a person to leave an organization arête seek new opportunities. Generally the considered variables for leaving the job; low pay structure, low potential for growth, and unfair treatment by management and conflict with the immediate supervisor/ Coworkers. The factors considered for choosing the new job; chances of career growth, higher salary, job security, freedom at workplace, reputation of organization and higher position. Materials and methods: Study populations are the millennial working in private organizations of Kathmandu valley. For this study the convenience sampling method was chosen where the data was collected through the questionnaire. Data were collected using likert scale questionnaire, yes/no questions, multiple choice single response and multiple choice multiple response questions. Percentage and correlation matrix was used to analyse the data,. Results: The outcome of the research indicates that main reason behind millennial leaving the organization is no growth opportunity and attraction towards new job is career growth. The employees chose the current organization either they are getting higher position or sensize future growth.